A longitudinal analysis of the extent and manner of representations of nature of science in U.S. high school biology and physics textbooks. Issue 1 (16th June 2016) - Abd‐El‐Khalick, Fouad; Myers, John Y.; Summers, Ryan; Brunner, Jeanne; Waight, Noemi; Wahbeh, Nader; Zeineddin, Ava A.; Belarmino, Jeremy
Abstract: This study assessed the (i) ways in which, and extent to which, several aspects of nature of science (NOS) are represented in high school biology and physics textbooks in the United States (U.S.); (ii) extent to which these representations have changed over the course of several decades; and (iii) relative impact of discipline, and textbook publishers versus authors on the observed patterns. NOS aspects included the empirical, tentative, inferential, creative, theory‐laden, and social NOS; myth of "The Scientific Method"; nature of theories and laws; and social and cultural embeddedness of science. The sample included 34 (16 biology and 18 physics) textbooks, which commanded significant shares of the U.S. science textbook market. Textbooks were selected from seven "connected series" (three in biology and four in physics), which spanned 1–5 decades, with five series spanning, at least, 3 decades. Textbooks were scored for the accuracy and manner in which, as well as the extent (in textbook pages) to which, the target NOS aspects were represented. Analyses indicated that, on average, only less than 2.5% of the analyzed textbook pages were dedicated to addressing NOS constructs. Overall, representations of NOS in the textbooks did not differ by content area, were discernibly less than favorable, and did not improve substantially over the past several decades. These trends are incommensurate with the emphasis placed in U.S. reform efforts on helping precollege students develop informed NOS conceptions. Finally, the data strongly suggested that textbook authors have a relatively greater impact on the observed patterns when compared to textbook publishers. © 2016 Wiley Periodicals, Inc. J Res Sci Teach 54: 82–120, 2017